1991
DOI: 10.1007/bf01974270
|View full text |Cite
|
Sign up to set email alerts
|

In vitro production of pycnidia by Septoria tritici

Abstract: The in vitro production of pycnidia by Septoria tritici was examined on six media reported to induce the formation of fruiting bodies. Among 26 freshly isolated cultures from various parts of the world, consistent differences in growth type were found which were only partially influenced by nutritional and environmental conditions. Cultures with yeast-like growth produced hardly any pycnidia or pseudopycnidia, while cultures with intermediate or mycelial growth types produced them frequently. Incubation in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 8 publications
3
13
0
Order By: Relevance
“…Cultures were whitish to pink, convoluted yeast-like colonies, with black stroma-like structures and without formation of typical pycnidia. This is in accordance with observations of Hilu & Bever (1957), Djerbi et al (1974) and Kema & Annone (1991).…”
Section: Identity With S Tritici Anamorphsupporting
confidence: 94%
“…Cultures were whitish to pink, convoluted yeast-like colonies, with black stroma-like structures and without formation of typical pycnidia. This is in accordance with observations of Hilu & Bever (1957), Djerbi et al (1974) and Kema & Annone (1991).…”
Section: Identity With S Tritici Anamorphsupporting
confidence: 94%
“…In subsequent observations, no further formation of cirrhi from the pycnidia present on the damaged leaves was noticed. The subsequent observations of cirrhi under the microscope confirm the presence of conidia, morphologically attributable to Zymoseptoria tritici [32,33] ( Figure 2B). The crushing on the slide of the pycnidia, taken at 72-96 h, in the damaged leaf portions, and the subsequent observation under the microscope, did not allow us to observe any propagation element inside the corpuscle ( Figure 2C).…”
Section: Isolation Of Pathogens From Symptomatic Leavessupporting
confidence: 54%
“…In seasons with low rain at the end of the crop cycle (2017), cirrhi developed from pycnidia located on the leaves were very scarce [32,57], inducing a decrease in the cycles of infection; nevertheless, the late disease appearance seems to be the main reason for the low effect on yields, as demonstrated in 2016, when climate conditions were favourable to disease symptom expression [57].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that pycnidia are extensively melanized, suggesting that melanin is required for asexual fructification in M. graminicola (Duncan and Howard, 2000; Kema et al ., 1996; Mehrabi et al ., 2006). This may explain the failure to produce pycnidia in vitro , although this process is also influenced by other cultural conditions (Kema and Annone, 1991). In other filamentous plant pathogens, MgFus3 orthologues are essential in various stages of development, including vegetative growth, conidiation and germination of conidia (Lev et al ., 1999; Takano et al ., 2000; Zheng et al ., 2000).…”
Section: Discussionmentioning
confidence: 99%